The chronically inflamed central nervous system provides niches for long-lived plasma cells - Karolin Pollok; Ronja Mothes; Carolin Ulbricht; Alina Liebheit; Jan David Gerken; Sylvia Uhlmann; Friedemann Paul; Raluca Niesner; Helena Radbruch; Anja Erika Hauser (Acta Neuropathologica Communications, 2017)
Abstract Although oligoclonal bands in the cerebrospinal fluid have been a hallmark of multiple sclerosis diagnosis for over three decades, the role of antibody-secreting cells in multiple sclerosis remains unclear. T and B cells are critical for multiple sclerosis pathogenesis, but increasing evidence suggests that plasma cells also contribute, through secretion of autoantibodies. Long-lived plasma cells are known to drive various chronic inflammatory conditions as e.g. systemic lupus erythematosus, however, to what extent they are present in autoimmune central nervous system inflammation has not yet been investigated. In brain biopsies from multiple sclerosis patients and other neurological diseases, we could detect non-proliferating plasma cells (CD138+Ki67−) in the parenchyma. Based on this finding, we hypothesized that long-lived plasma cells can persist in the central nervous system (CNS). In order to test this hypothesis, we adapted the multiple sclerosis mouse model experimental autoimmune encephalomyelitis to generate a B cell memory response. Plasma cells were found in the meninges and the parenchyma of the inflamed spinal cord, surrounded by tissue areas resembling survival niches for these cells, characterized by an up-regulation of chemokines (CXCL12), adhesion molecules (VCAM-1) and survival factors (APRIL and BAFF). In order to determine the lifetime of plasma cells in the chronically inflamed CNS, we labeled the DNA of proliferating cells with 5-ethynyl-2′-deoxyuridine (EdU). Up to five weeks later, we could detect EdU+ long-lived plasma cells in the murine CNS. To our knowledge, this is the first study describing non-proliferating plasma cells directly in the target tissue of a chronic inflammation in humans, as well as the first evidence demonstrating the ability of plasma cells to persist in the CNS, and the ability of the chronically inflamed CNS tissue to promote this persistence. Hence, our results suggest that the CNS provides survival niches for long-lived plasma cells, similar to the niches found in other organs. Targeting these cells in the CNS offers new perspectives for treatment of chronic autoimmune neuroinflammatory diseases, especially in patients who do not respond to conventional therapies.